2001
DOI: 10.1007/s002590100501
|View full text |Cite
|
Sign up to set email alerts
|

The clinical value of 18F-FDG detection with a dual-head coincidence camera: a review

Abstract: Positron emission tomography (PET) has evolved into a technique that can accurately determine the distribution of positron-emitting radionuclides. The addition of a coincidence detection mode to a standard dual-head detector system has resulted in the option of single-photon and annihilation coincidence detection. This new device for imaging fluorine-18 2-fluoro-2-deoxy-D-glucose (18F-FDG) accumulation in neoplasms became commercially available in 1994. Besides conventional low-energy imaging in the collimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0
3

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 118 publications
2
16
0
3
Order By: Relevance
“…Furthermore, growth factor deprivation leads to a drop in glycolysis, Glut1 expression, and intracellular ATP, all of which contribute to cell death (11,12). However, although these pathways have been studied in tumor cell lines, and the aerobic glycolysis phenotype has been shown to contribute to the malignant state (13), little is known regarding the particular requirement for glucose-dependent metabolism for TCR signaling and effector functions in normal T lymphocytes.…”
Section: P Ost-thymic Cd8mentioning
confidence: 99%
“…Furthermore, growth factor deprivation leads to a drop in glycolysis, Glut1 expression, and intracellular ATP, all of which contribute to cell death (11,12). However, although these pathways have been studied in tumor cell lines, and the aerobic glycolysis phenotype has been shown to contribute to the malignant state (13), little is known regarding the particular requirement for glucose-dependent metabolism for TCR signaling and effector functions in normal T lymphocytes.…”
Section: P Ost-thymic Cd8mentioning
confidence: 99%
“…FDG-PET has also been used for prognostic evaluation, for monitoring tumor therapy, and for early detection of recurrent cancer growth (2,29,33). 13 C magnetic resonance spectroscopy (MRS) with use of enriched [ 13 C]glucose can also serve to monitor in vivo glucose metabolism.…”
mentioning
confidence: 99%
“…Furthermore, quantitative studies of biopsies from human cancers have indicated a positive correlation between tumor lactate concentration and incidence of metastasis (5,26,34,35). Increased glycolysis is associated with higher glucose uptake and metabolism, and it is now utilized as an indicator of malignancy by applying positron emission tomography (PET) with the glucose analog 2-[ 18 F]fluoro-2-deoxy-D-glucose (FDG) (2,23,29,33). FDG-PET has also been used for prognostic evaluation, for monitoring tumor therapy, and for early detection of recurrent cancer growth (2, 29, 33).…”
mentioning
confidence: 99%
“…In the 2 patients with false negative results, histopathological examination demonstrated solitary involved nodes, the tumour deposits measuring 5 and 4 mm, respectively. Such small lesions are below the resolution of GCPET, which is limited by partial volume effects (29). The results also highlighted the efficacy of GCPET, sited in a district general hospital, to detect axillary lymph node metastases with high specificity in women with large and LABCs.…”
Section: Discussionmentioning
confidence: 80%